Mechanisms of action of bile acids in pediatric gastroesophageal reflux: Exploration through non-targeted and targeted metabolomics methods - Linqian Zhang; Kang Wang; Qianwen Shi; Panjian Lai; Haiying Fang; Yuhe Chen; Xiaobing Li (PLoS ONE, 2026)
Purpose To investigate the pathogenesis of pediatric bile reflux gastritis (BRG) using non-targeted and targeted metabolomics analyses of the changes and content differences of bile acids (BAs) in gastric juice. Methods Data from 25 pediatric BRG patients treated at Jinhua Maternal and Child Health Care Hospital between May 2022 and August 2023 were retrospectively analyzed. Twenty-five patients with gastritis without bile reflux and 25 healthy controls were selected for the comparison of total bile acids (TBA) levels of gastric juice and peripheral blood and the identification of differential metabolites. The correlations of gastric juice and peripheral blood TBA levels with the clinical characteristics of the pediatric BRG patients were analyzed. ROC curves were constructed to evaluate the diagnostic performance of TBA in identifying BRG, as indicated by the area under the curve (AUC), sensitivity, and specificity. Results Identification and quantitative metabolomics Studies have identified the top 10 differential metabolites in gastric juice between the BRG and healthy control groups, which include fatty acids, phospholipids, 23-carbon compounds, amines, vitamins, steroids, peptide hormones, monosaccharides, polyketides, and non-ribosomal peptides. This indicated that glycerophospholipid metabolism, prodigiosin biosynthesis, lysine degradation, glycerolipid metabolism, and primary BA biosynthesis were the most relevant pathways. Differential metabolites were primarily concentrated in the T helper 17 (Th17) cell differentiation pathway (P < 0.05, effect value>0.1). Conclusion The metabolites and metabolic pathways identified in different groups will aid in elucidating the pathogenic mechanisms underlying pediatric BRG. Gastric juice and peripheral blood TBA levels showed a trend of aberrant expression in pediatric BRG patients, potentially guiding clinical diagnosis.